(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Whey is one of the most representative residues of the dairy industry and one of the most severe pollutants that exist at the environmental level. However, the amount of lactose present in this by-product makes it possible to obtain products with a high commercial value, such as lactic acid, through bioconversion processes. In this sense, the main objective of this research was to evaluate the kinetic parameters of lactic acid production from whey using Lactobacillus casei. The whey was enriched with lactose as the main source of carbohydrate, in order to optimize its consumption, in the whole and deproteinized whey. With the results obtained experimentally, a completely randomized design with a complete 2x4 factorial arrangement was established, thus obtaining the combined effect of the factors to establish the optimal values ​​of the kinetics of lactic acid production in relation to biomass concentration, consumption of substrate and product formation. The deproteinized whey at 1% lactose, yielded the highest acidity value (10 g / l of lactic acid), the highest and biomass yield with respect to the substrate (Yx / s) was obtained in the enriched whole whey at the level of lactose concentration corresponding to 10% (39,5 g of biomass for each gram of substrate consumed), observing that the concentration of biomass increases with the concentration of lactose. However, high concentrations of lactose inhibit lactic acid production.